A Review of White Spot Lesions: Development and Treatment with Resin Infiltration - Alexandra Maria Prada; Georgiana Ioana Potra Cicalău; Gabriela Ciavoi (Dentistry Journal)
White spot lesions (WSLs) are demineralized lesions of the enamel that form in the presence of bacterial plaque, affecting the aesthetics by modifying the refractive index of the enamel, giving the characteristic “chalky” aspect. They have various causes, including fixed orthodontic treatments, improper hygiene, fluorosis and genetic factors. Background/Objectives: Considering the latest need for dental aesthetics and the popularization of fixed orthodontic treatments, the need to effectively treat WSLs has increased. The objective of this research is to review the development of WSLs and their treatment with resin infiltration. Methods: The PubMed, Web of Science, Scopus and Google Scholar databases were searched for relevant reviews and studies. Out of all, 56 were included in this research. Results: Prophylactic measures, such as fluorized toothpaste and varnishes, have limited results. Standard caries treatment is too invasive as it removes too much healthy enamel for obturation retentivity. The resin infiltration resin process does not require drilling or tooth structure loss, making it a painless and minimally invasive treatment. The resin used has a refractive index comparable to that of healthy enamel, consequently restoring aesthetics and ensuring the prevention of caries evolvement. The treatment involves five important steps: prophylaxis, acid demineralization, alcohol drying, resin infiltration and UV light curing. Depending on the clinical case, the demineralization and drying steps may need to be repeated. Conclusions: Infiltrations with resin are painless and well tolerated by patients. Out of all minimally invasive treatments, they have an immediate satisfactory outcome, with results stable for a minimum of 45 months.